Mental Accounting dengan Memaknai Kondisi Keuangan Mahasiswa Pasca Pandemi Covid-19 - Ardimansyah .; Elga Yulindisti; Rafles Ginting (Jurnal Pendidikan Akuntansi (JPAK), 2023)
The outbreak of the Covid-19 pandemic has had a negative impact on the economic development of society. This has also affected the financial condition of all sectors of the population. Students are one of those who can be categorized as consumers, who tend to spend money excessively and need to adjust their lifestyle in managing their finances. This study aims to investigate how students can understand their financial condition before and after the Covid-19 pandemic through a mental accounting-based thinking. Using a descriptive qualitative method, this research analyzes based on a phenomenological study of students and experiences the change in financial condition after the pandemic that has occurred in Pontianak. The information collection in this research uses interview sessions and observes the informants' life aspects through social media. Through the survey conducted, the results of the research show that the phenomenon before and after Covid-19 related to students treating their financial condition and decision-making from the income received. Students experience the beneficial influence in their financial allocation thoughts by applying mental accounting. By implementing mental accounting, students can have better thoughts about how to manage their finances after the Covid-19 pandemic.